2017
DOI: 10.1155/2017/8062924
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Scar Endometriosis: An Uncommon Surgical Complication on the Rise? Case Report and Literature Review

Abstract: Endometriosis is defined by the presence and growth of ectopic functional endometrial tissue outside the uterus. Scar endometriosis has been described following obstetrical and gynecological surgery. It is a rare condition, though probably on the rise, due to the considerable increase of cesarean sections performed worldwide. Its physiopathology is complex; its symptomatology is rich and diverse but thorough clinical examination along with ultrasound imaging and potentially pretherapeutic cytologic evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Although the risk factors for scar endometriosis are not well known, it has been shown that previous uterine surgery, especially CS, is the most common risk factor for this condition [10,11]. As a possible cause of AWE after CS, the iatrogenic implantation of endometrial tissue into the abdominal fascia and subcutaneous tissue during the procedure has been suggested [12]. However, this theory does not explain the development of endometriosis in distant organs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk factors for scar endometriosis are not well known, it has been shown that previous uterine surgery, especially CS, is the most common risk factor for this condition [10,11]. As a possible cause of AWE after CS, the iatrogenic implantation of endometrial tissue into the abdominal fascia and subcutaneous tissue during the procedure has been suggested [12]. However, this theory does not explain the development of endometriosis in distant organs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the invasive modes cells adopted using the 3-D spheroid model but not single cells on ECM could, for the first time, reproduce collective-migration phenotypes previously identified only through histological and clinical observations, further confirming the relevance of this model. Several clinical studies suggested endometriosis can only implant in damaged tissues 33,34,35 . To investigate this in vitro, we mimicked the intact tissue using the basement membrane mimic Matrigel and scar-tissue mimic collagen I.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies authors suggested that FNAC can be the option for the definitive diagnosis of scar endometriosis prior to surgical intervention. On the contrary, in other studies the authors didn't encourage to use this technique as a diagnostic tool because with this procedure there is an increased risk of de-novo endometriotic implants at the puncture site, as well as organ injury if the diagnosis is uncertain 6,8,11 . Wide local surgical excision with 1 cm negative margin is the most recommended treatment modality for the scar endometriosis.…”
Section: Figure: 3 a And 3b Gross Photograph Showing Wide Excision Of Tmentioning
confidence: 99%